Linguistic Modelling of the Eco-Economic WATER Concept in the EU Water Framework Directive - Kovalyk, Nataliia; Tymochko, Lesia (Respectus Philologicus, 2026)
This study examines how the EU Water Framework Directive conceptualises WATER, highlighting an imbalance between definitional stability and functional representation within regulatory discourse. Although environmental discourse has been widely studied, systematic cognitive modelling of the EU water policy remains limited. The study aims to identify the semantic roles that shape the conceptual profile of the eco-economic WATER concept in the Water Framework Directive. The eco-economic WATER concept is defined as a linguistically encoded and institutionally framed construct integrating ecological values with economic considerations within EU environmental governance. It is hypothesised that the Directive constructs WATER as a hybrid entity dominated by the Formal and Constitutive Qualia roles, while the Agentive and Telic roles are selectively activated in specific governance contexts. The analysis applies frame-based and Qualia-based modelling within Generative Lexicon Theory, supported by frequency analysis and chi-square testing. The findings demonstrate a predominance of the Formal (32.5%) and Constitutive (31.2%) roles and lower frequencies of the Agentive (19.3%) and Telic (17.0%) roles, indicating a systematic conceptual asymmetry shaped by institutional and regulatory priorities. The Directive thus prioritises classificatory precision and measurable attributes of WATER, reinforcing a governance model centred on monitoring and regulatory control. Future research may extend Qualia-based modelling to more recent EU water policy instruments in order to trace shifts in conceptualisation across evolving governance frameworks.